A comparative evaluation of conjunctival autograft and intra- operative mitomycin-C in the management of primary pterygium- our experience - Shet, Satish D.; Gupta, Piyush S. (International Surgery Journal, 2017)
Background: Surgery is the treatment of choice in the management of primary pterygium. Recurrence following excision is frustrating to both the surgeons and patients alike. India being a tropical country is an ideal home for pterygium. Methods: This study was carried out in a tertiary care hospital. A comparative prospective study was performed in 80 patients presenting with primary pterygium who fulfill inclusion and exclusion criteria were taken for the study for the period from January 2011 to December 2012. They were randomised in two equal groups to undergo primary pterygium surgery with conjunctival autograft and excision of primary pterygium followed by intraoperative use of Mitomycin-C for 3 minutes to study the effectiveness of adjuncts i.e. mitomycin -C and conjunctival autograft in preventing recurrence of pterygium after excision and complications following the procedure. Follow up visits were scheduled for the postoperative days 1, 7, 30 days and 3 and 6 months. mean follow up was for 9 months. Results: No significant intra operative complications were noted except for 2 cases of button holing of the conjunctival graft. Recurrence was noted in 1 case after conjunctival autograft and 1 case in mitomycin C group. Conclusions: The adjuncts in primary pterygium surgery as conjunctival autograft and pterygium excision with mitomycin-C significantly reduces the recurrence rates than bare sclera excision alone.